Recent Trends in the Development and Application of Nano-Antioxidants for Skin-Related Disease - Yi Xue; Tao Wang; Ji-Peng Liu; Qi Chen; Xiao-Long Dai; Min Su; Yu-Hang Cheng; Cheng-Chao Chu; Yun-Qing Ren (Antioxidants)
Skin is a vital barrier for the human body, protecting against external environmental influences and maintaining internal homeostasis. In addition, an imbalance of oxidative stress and antioxidant mechanisms can lead to skin-related diseases. Thus, for treating skin-related diseases, antioxidant therapy may be an important strategy to alleviate these symptoms. However, traditional drug therapies have limitations in treating these conditions, such as lack of lasting effect and insufficient skin permeability. Recently, nano-antioxidants, with their good permeability, sustained-release ability, multifunctionality, and other beneficial characteristics, have showed their advances in the exploration of skin-related diseases from research on safe therapies to clinical practice. Hereby, we review the latest research and advancements in nano-antioxidants for skin-related diseases. We categorize skin-related diseases into four main groups: skin inflammatory diseases, skin damage caused by ultraviolet rays, skin wound healing, and other skin-related conditions. Additionally, we summarize the prospects and potential future directions for nano-antioxidant drugs in treating skin-related diseases.